ISOLATION, MOLECULAR CHARACTERIZATION AND APPLICATION OF PENICILLIUM CITRINUM AS BIOFERTILIZER POTENTIALS TO ENHANCE COWPEA GROWTH - Egelonu, S. C.; Fabian, U. M.; Ikechi-Nwogu, Chinyerum G. (FUDMA JOURNAL OF SCIENCES, 2024)
Chemical fertilizers are linked to a persistent decline in soil fertility, posing health hazards. This study investigated P. citrinum as a biofertilizer for cowpea (Vigna unguiculata growth. The test fungus was identified using molecular techniques from alligator pepper. Using a pot experimental method, an in-situ experiment was conducted on cowpea (TVX-3236) in the greenhouse to screen for the isolate's mycofertilizer potential. For six weeks, the cowpea was planted in six replicates in loamy soil. P. citrinum treatment was applied to the cowpea leaves in the following amounts 20 ml, 35 ml, 50 ml, 65 ml and 80 ml per bucket at a concentration of 0.08 spores per milliliter (mL) with no inoculation on the control. P. citrinum was applied on the second week and data was collected for agronomic traits (plant height, leaf number, leaf area, and root length) and leaf color. The impact of P. citrinum on cowpea height, leaf number, leaf area, and root length revealed that these agronomic parameters rose with increasing P. citrinum concentration. The cowpea in the pot that received the 80 ml P. citrinum inoculation performed the best, indicating that the plant benefited from this treatment. The experiment's results suggest that the isolate can be utilized as a mycofertilizer to promote cowpea growth. For that reason, this study offers some initial data for further investigation into the application of P. citrinum as a biofertilizer in agriculture. This fungus strain's capacity to stimulate plant development may aid in the preservation and revegetation of some vegetations.
Keywords: Fungi; Molecular techniques; Penicillium citrinum; Biofertilizer; Rhizosphere; Cowpea